Secular and Cyclical Changes in the Demand for Components of a Product Cluster - Douglas, Edna (The Review of Economics and Statistics, 1967)
T HE DEMAND for consumer durables has been of particular interest to economists because of cyclical and irregular variations in purchases. Sales cycles of considerable amplitude are associated, in part, with the accelerator effect of an annual consumer purchase-stock I ratio of less than 1.00, in combination with the consumer's ability to exercise considerable discretion in choosing the time for making replacement purchases. One cluster of consumer durables household laundry appliances has not been subjected to extensive study, yet seemed to offer promising possibilities for analysis.2 Viewed technically, four products comprise the cluster: the wringer washer, the automatic washer, the combination washer-dryer, and the dryer. The principal item in this group is the washer and, since 1952, the automatic washer. From an economic viewpoint, the components of this cluster can be classified according to their market maturity and according to their complementary or competing relationship to one another in purchase and in use. We shall define a product as one for which there has not previously been a close substitute. The washing machine of the 1920's was new in its use of nonhuman sources of energy electricity or gas. We do not include in any portion of our analysis laundry equipment which was totally dependent upon manual operation even though its use may have continued after introduction of the electric and gas machines. A product can be said to have reached market maturity when the rate of increase in its use by consumers has begun to decline. With a durable good, this occurs when the rate of increase in ownership begins to decline.3 We shall define an innovation as a major change in the attributes of a product. The automatic washer and combination washerdryer can be classified as innovations, representing major changes in the electric washer, in contrast to relatively minor improvements in the wringer-such as drains, timers, electric wringers -and later in the automaticsuch as programmed temperature, speed, and dispenser controls. To the consumer, the marginal utility of an innovation is far greater than that of an improvement. The demarcation between the two can be established best in terms of consumers' market behavior toward the product or their use of it. A successful innovation in durable goods is one which causes the ownership (and use) rate to rise to a level equal to or greater than that of its predecessor, and this usually occurs at the expense of the predecessor product. An abortive innovation is evident when product ownership rises but then declines before reaching the level achieved by the predecessor product. A declining product is identified by an absolute decrease in rate of ownership. The meaning of competing and complementary products in this study is consistent with that in general use in demand analysis. * Scientific Paper No. 2539 (Washington Agricultural Experiment Stations, Pullman), Project 1496. The author is indebted to Shaikh M. Ghazanfar, who assisted in all phases of the statistical analysis and was responsible for many of the calculations and for all of the graphs; to Rosemary Baker, who was responsible for assembling many of the original data; and to Jagjit Dhesi, who assisted in the calculations. Henry J. Carey and the late Marguerite Cook of the Market Research Department of Merchandising Week, were kind in providing considerable statistical data from their files, and Guenther Baumgart, President of the American Home Laundry Manufacturers' Association, generously made available the association's annual reports of distributors' sales of laundry appliances by states. The author is especially grateful to her colleagues, William Iulo and Harry McAllister, who, through a number of constructive criticisms, helped to correct and refine the analysis and increase the clarity of presentation. 'Throughout this paper, stock and inventory refer to consumer stocks (or inventories) rather than business stocks (or inventories) unless otherwise indicated. 'The most extensive study which has been published is by Spencer and Mattheiss [22]. More limited attention has been given to washing machines in [2] and [7]. Historical reviews can be found in [20] and [21]. 'Since in this paper both ownership and purchases are specified as a proportion of number of households or of population, the relevant rate of change is rate of change in ownership ratio. Members of the appliance industry commonly refer to this ownership ratio as saturation level.